Powerful partnership: crosstalk between pannexin 1 and the cytoskeleton - Boyce, Andrew K.; Wicki-Stordeur, Leigh E.; Swayne, Leigh Anne (Frontiers in Physiology, 2014)
Pannexin 1 (Panx1) large-pore ion and metabolite channels are emerging as key proteins in many physiological and pathophysiological scenarios. Recent evidence has tightly linked Panx1 trafficking and function to the cytoskeleton, a multi-component network that provides critical structural support, transportation, and scaffolding functions in all cell types. Here we review early work demonstrating the mechanosensitive activation of Panx1 channels, and expand on more recent evidence directly linking Panx1 to the cytoskeleton. Further, we examine the reciprocal regulation between Panx1 and the cytoskeleton, and discuss the involvement of Panx1 in cytoskeletal-regulated cell behaviors. Finally, we identify important gaps in the current knowledge surrounding this emerging Panx1-cytoskeleton relationship.